Harvesting Health Knowledge: Breast Cancer Perceptions in the South Florida Latinx Farmworker Community. (July 2021) - Casanova, Felicia; Knaul, Felicia M.; Rodriguez, Natalia M.
South Florida agricultural regions, home to Latinx immigrant farmworkers, report higher rates of late-stage breast cancer diagnosis than national, state, and county-level averages. We conducted a community-based qualitative study on the needs, health knowledge gaps, barriers to breast cancer screening, and the role of community health workers (CHWs) in supporting the community's access to early detection services. We conducted three CHW focus groups (FGs) ( n = 25) and in-depth interviews ( n = 15), two FGs ( n = 18) and in-depth interviews ( n = 3) with farmworker community members, and informal interviews with cancer clinicians ( n = 7). Using a grounded theory approach, five core themes regarding the community's barriers to accessing health care services emerged: (a) lack of information; (b) social and economic barriers; (c) cultural factors; (d) fears and mistrust; and (e) psychosocial concerns. Findings yield implications for community health practice, the potential impact of CHWs, and the production of breast cancer education to improve health equity along with the care continuum.